CREATING INTERACTIVE WORD WALLS TO HELP ELEMENTARY SCHOOL STUDENTS’ VOCABULARY MASTERY - Rani Febrina; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
The increasing of global communication makes the demand to mastering English also increase, including Indonesia. In learning English, understanding vocabulary is considered as an essential thing because without vocabulary, people will not be able to express their ideas and comprehend what other people say, in other words, they are not able to communicate each other. In order to mastering English vocabulary, students from elementary grade are introduced to English vocabulary by using many kinds of interactive media that can help this purpose. One of the media to help students’ vocabulary mastery is called Interactive Word Walls which is used in elementary school. Interactive Word Walls is a vocabulary learning media where the words that have been learned are displayed on the wall. This paper will discuss the procedure in creating this media, the application method, and the use of it.